Evaluation of universal basic education quality indicators towards solid foundation for education in Nigeria (2023)
Nigeria was granted independence by the British in the year 1960. It took some time before her educational system was developed as Nigeria operated an educational policy inherited from Britain which was not sustainable to take Nigeria to the Promised Land. This notwithstanding, the foundations were laid for a new policy. From available literature, school enrolment ratio in primary school was as high as 80%, but dropped to a mere 25% by the time children reached secondary school. Education infrastructure deteriorated and neglected as classrooms, laboratories, workshops, sporting facilities, equipment, libraries were in a state of total decay. The physical condition of most public schools was seen to be pathetic. This study assessed the Universal Basic Education Quality indicators towards Solid Foundation for Education in Nigeria. Four research questions was raised and answered. Two structured and validated instruments were used for data collection from three hundred basic education teachers and thirty UBEC staff. Data collected was analysed using descriptive and inferential statistics. The results showed that the Antecedent Indicators (AI) and the Transaction Indicators (Tl) evaluated in this study was statistically significant {F(l 83,299) = 2.295, p = .000, a = 0.05}. It is recommended that adequate attention in quantitative and qualitative terms as at when due should be given to them to ensure that the universal conception of Universal Basic Education scheme and its attendant objectives are not only achieved but improved upon at all times.